A novel optimization framework for controlling stabilization issue in design principle of FinFET based SRAM - Girish H; Shahshikumar D. R (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The conventional design principle of the finFET offers various constraints that act as an impediment towards improving ther performance of finFET SRAM. After reviewing existing approaches, it has been found that there are not enough work found to be emphasizing on cost-effective optimization by addressing the stability problems in finFET design.Therefore, the proposed system introduces a novel optimization mechanism considering some essential design attributes e.g. area, thickness of fin, and number of components. The contribution of the proposed technique is to determine the better form of thickness of fin and its related aspect that can act as a solution to minimize various other asscoiated problems in finFET SRAM. Implemented using soft-computational approach, the proposed system exhibits that it offers better energy retention, lower delay, and potential capability to offer higher throughput irrespective of presence of uncertain amount of noise within the component.